The Influence of Self-Efficacy, Optimism, Hope, Resilience on The Affective Commitment of Hospital Staff - I Wayan Aditya Tariana; Titin Suhartini; Doddy Fernando Pausoan Gultom; Destiana Kumala; Ahmad Ansyori (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Affective commitment of hospital staff plays an important role in the health service sector. This research aims to determine the influence of self-efficacy, optimism, hope and resilience on the affective commitment of hospital staff. The study population was 383 hospital staff from two different hospitals. Sampling was carried out using stratified random sampling to represent both hospital populations. The data analysis method was carried out using PLS SEM. The research results found that self-efficacy, optimism, hope had a significant positive effect on affective commitment while resilience had no significant effect on affective commitment. This research contributes to the importance of psychological capital dimensions in increasing affective commitment among hospital staff in the health sector.